Rehabilitation Improves Behavioral Recovery and Lessens Cell Death Without Affecting Iron, Ferritin, Transferrin, or Inflammation After Intracerebral Hemorrhage in Rats. (May 2014) - Caliaperumal, Jayalakshmi; Colbourne, Frederick
Background. Rehabilitation aids recovery from stroke in animal models, including in intracerebral hemorrhage (ICH). Sometimes, rehabilitation lessens brain damage. Objective . We tested whether rehabilitation improves recovery and reduces perihematoma neuronal death. We also evaluated whether rehabilitation influences iron toxicity and inflammation, mediators of secondary degeneration after ICH. Methods . Rats were trained to retrieve food pellets in a staircase apparatus and later subjected to striatal ICH (via collagenase infusion). After 1 week, they were given either enriched rehabilitation (ER), including reach training with group housing and environmental enrichment, or control treatment (group housing). Rats in the first experiment were treated for 2 weeks, functionally assessed, and killed humanely at 1 month to determine brain levels of nonheme iron. A second experiment used a similar approach, except that animals were euthanized at 14 days to evaluate perihematoma neuronal death (FluoroJade), iron distribution (Perls), and astrocyte (GFAP) and microglia (Iba-1) activity. A third experiment measured levels of iron-binding proteins (ferritin and transferrin) at 14 days. Results . Striatal ICH caused functional impairments, which were significantly improved with ER. The ICH caused delayed perihematoma neuronal death, which ER significantly reduced. Hemispheric iron levels, the amount of iron-binding proteins, and perihematoma astrocytes and microglia numbers were significantly elevated after ICH (vs normal side) but were not affected by ER. Conclusions . Rehabilitation is an effective behavioral and neuroprotective strategy for ICH. Neither effect appears to stem from influencing iron toxicity or inflammation. Thus, additional work must identify underlying mechanisms to help further therapeutic gains.